CONTEXTUALIZING RESTORATIVE JUSTICE THROUGH DIVERSION MECHANISM: A STUDY OF INDONESIA JUVENILE JUSTICE SYSTEM - Rahman, Faiz (Indonesia Law Review, 2019)
Implementation of restorative justice in the juvenile justice system in many countries has undergone its dynamics in the past few decades, including in Indonesia. The enactment of Indonesia Juvenile Justice System Law in mid-2014, which invalidates the 1997 Juvenile Court Law, became a significant point of juvenile justice reformation in Indonesia. The new Law began to shift the retributive paradigm in the Juvenile Court Law, as the previous statutory basis for juvenile justice in Indonesia, to restorative justice paradigm. The new Law introduces the Diversion mechanism as a means to implement the restorative justice approach. This article seeks to discuss how restorative justice can be contextualized through diversion mechanism, as well as to consider whether the new Indonesia Juvenile Justice System utilises restorative justice in a marginalized, boutique, or tokenistic way. Furthermore, this article uses statutory and theoretical approaches to examine the contextualization of restorative justice through the diversion mechanism introduced in the new Juvenile Justice System Law.